Ø§Ù„Ø³Ù†Ø© Ø§Ù„Ù†Ø¨ÙˆÙŠØ© ÙˆØ§Ù„Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙŠØ© Ø¹Ù†Ø¯ Ø§Ø¨Ù† ØØ²Ù… Ø§Ù„Ø£Ù†Ø¯Ù„Ø³ÙŠ - Arafat, Ahmad Tajuddin (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2017)
The Qur'an and the Sahih Hadith interwave each other. Both correspond and there is no contradiction between the two for both are part of God's revelation toward Prophet Muhammad. Therefore, they are referred as sacred texts to seek guidance from. According to Ibn Hazm (d.456 AH), the sacred text must be understood textually. He treated the text as it is in the Qur'an and Sunna denoting the law of something. It is unacceptable for him to use majaz (metaphorical interpretation) except a famous majaz evidenced by other texts, ijma', sensory elements, or the language by which the text is derived. Because of this textual tendency, the Sunna / Hadith that has the power of hujjah (a valid argument) is only in the form of his sunnah qauliyyah (stated sunnah). Meanwhile, his sunnah fi'liyyah (performed sunnah) can not be used as hujjah unless it correlates with the command written in the Qur'an and Sunnah (qauliyah). The sunnah taqririyyah (confirmed sunnah), according to Ibn Hazm, is only addressed to mubahÂ (lawful) category and has no binding legal provisions.